A Novel Plant-Based Nutraceutical Combined with Exercise Can Revert Oxidative Status in Plasma and Liver in a Diet-Induced-Obesity Animal Model - Ana Guzmán-Carrasco; Garyfallia Kapravelou; María López-Jurado; Francisco Bermúdez; Eduardo Andrés-León; Laura C. Terrón-Camero; José Prados; Consolación Melguizo; Jesus M. Porres; Rosario Martínez (MDPI AG, 2024)
The prevalence of obesity increases alarmingly every year mostly due to external factors such as high-fat and high-refined sugar intake associated with a sedentary lifestyle. It triggers metabolic disorders such as insulin resistance, hyperlipemia, non-alcoholic fatty liver disease, chronic inflammation, oxidative stress, and gut microbiota dysbiosis. The aim of this study was to evaluate the beneficial effects of a combined intervention with caloric restriction, nutraceutical intake, and a mixed training protocol on oxidative stress, inflammation, and gut dysbiosis derived from the development of obesity in a C57BL6/J mouse experimental model of diet-induced obesity (4.6 Kcal/g diet, 45% Kcal as fat, and 20% fructose in the drinking fluid). The nutraceutical was formulated with ethanolic extracts of Argania spinosa pulp (10%) and Camelina sativa seeds (10%) and with protein hydrolysates from Psoralea corylifolia seeds (40%) and Spirodela polyrhiza whole plants (40%). The combination of nutraceutical and exercise decreased the animals' body weights and inflammatory markers (TNFα, IL-6, and resistin) in plasma, while increasing gene expression of cat, sod2, gsta2, and nqo1 in the liver. Obese animals showed lower β-diversity of microbiota and a higher Firmicutes/Bacteroidetes ratio vs. normocaloric controls that were reversed by all interventions implemented. Dietary inclusion of a nutraceutical with high antioxidant potential combined with an exercise protocol can be beneficial for bodyweight control and improvement of metabolic status in patients undergoing obesity treatment.